(untitled) (APPLICATION: Applied science in Learning Research, 2022)
The purpose of this study was to determine the design and feasibility of STEM-based learning videos with the topic of identifying Escherichia coli bacteria in well water. This type of research is research & development with a 4D development model. but this research focuses on 3 stages, namely define, design, and development. The research subjects were students of the 6th semester of Biology Education Study Program with a total of 7-10 students as respondents. The validation test uses 3 validators who validate the material and media. The data collection instrument used a validation questionnaire and a student response questionnaire. The results of the data obtained indicate that the STEM-based learning video product related to Escherichia coli bacteria in well water is in the "Eligible" category with a percentage of material elements of 72% and media elements of 78%. For student responses, it shows the enthusiasm of students to use this product for learning media with a percentage of 80.5%. This product is expected to be used in learning activities to see the effectiveness of the product on student learning outcomes. This learning video product can be used as a variety of learning resources.